The Effects of Adding Hempseed Cake on Sperm Traits, Body Weight, Haematological and Biochemical Parameters in Rabbit Males - Baláži, Andrej; Svoradová, Andrea; Kováčik, Anton; Vašíček, Jaromír; Chrenek, Peter (Veterinary sciences, 2024)
Incorporating of agro-industrial co-products into animal nutrition could represent an opportunity to lessen the environmental impact of the food production chain. One such co-product is a hempseed cake originating from cold pressing hemp seeds to extract oil for human consumption. The aim of the present study was to evaluate the action of hempseed cake in the diet on male rabbit reproductive and some non-reproductive indexes. Male rabbits were fed either a standard diet (control group; C; n = 10) or a diet enriched with hempseed cake (experimental group E5 with 5% of a hempseed cake; n = 10, and experimental group E10 with 10% of a hempseed cake; n = 10) in 100 kg of the milled complete feed mixture. Rabbit weight gain, sperm concentration, motility, progressive motility, and sperm quality were evaluated using CASA and flow cytometry. Feeding with a hempseed cake, given at both tested concentrations, had no effect on weight gain per week and the total average weight gain compared to the control group (p > 0.05). Hempseed cake addition had no effect on sperm concentration in ejaculate, sperm motility, and progressive motility (p > 0.05). Selected haematological and biochemical indexes were examined. The E5 group showed positive tendencies in hepatic profile parameters, while in the E10 group the tendencies were opposite, though within the reference values. Based on our results, no negative effects of hempseed cake feeding on rabbit reproduction and health status were found, and we can recommend the use of hempseed cake at doses up to 10% in the nutrition and feeding of rabbits. Therefore, agro-industrial co-products can decrease the feeding cost.
Keywords: health status; semen quality; performance; Oryctolagus cuniculus; hempseed cake; nutrition